1992
DOI: 10.1111/j.1600-051x.1992.tb00653.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 4 days of mouth rinsing with delmopinol or chlorhexidine on the vitality of plaque bacteria

Abstract: Delmopinol is a new surface active anti-plaque agent that has demonstrated a low antimicrobial effect in vitro. By use of a vitality staining technique, the antimicrobial effect on bacteria in plaque samples was tested after rinsing with delmopinol or chlorhexidine. 6 healthy male subjects volunteered to rinse for 4 days using a double-blind cross-over study design with a wash-out period between the rinsing regimens. No oral hygiene measures were allowed during the test periods and each test period started wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
37
1
4

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 4 publications
5
37
1
4
Order By: Relevance
“…Therefore comparisons concerning vitality values can only be made in general. Mean vitality values ranged from 64 to 77%, which is in line with the findings of two studies following cultivation of dental plaque bacteria of healthy volunteers [Gordon et al, 1971;Manganiello et al, 1977], both employing the vital fluorescence technique [Netuschil et al, 1989;Rundegren et al, 1992;Arweiler et al, 2002].…”
Section: Discussionsupporting
confidence: 67%
“…Therefore comparisons concerning vitality values can only be made in general. Mean vitality values ranged from 64 to 77%, which is in line with the findings of two studies following cultivation of dental plaque bacteria of healthy volunteers [Gordon et al, 1971;Manganiello et al, 1977], both employing the vital fluorescence technique [Netuschil et al, 1989;Rundegren et al, 1992;Arweiler et al, 2002].…”
Section: Discussionsupporting
confidence: 67%
“…The viability of a 3-day-old plaque was reduced to 24% 2 h after two consec utive mouthrinses with 1.1 mM CHX as compared with 85% living microorganisms at baseline [Netuschil et al, 1989], Pre-rinse values were reached 8 h after mouthrinsing [Ne tuschil et al, 1989] which is in accordance with the above calculations. Recent findings indicate that prolonged use of CHX may have an even more pronounced long-term bacter icidal effect than that of a single mouthrinse [Rundegren et al, 1992], Though the present results and considerations oppose the interpretation of previous findings which led to the as sumption that the prolonged bacteriostatic effect was cru cial for the inhibitory effects of a mouthrinse with either 0.55 or 2.2 mM CHX. Oppermann [1979 actually suggested that the immediate antiglycolytic effect of a 2.2-mM CHX mouthrinse might be due to a bactericidal effect on plaque microorganisms.…”
Section: Discussioncontrasting
confidence: 56%
“…1979;Netuschil et al, 1989;Rundegren et al, 1992], The duration o f the bactericidal effect depends on the actual doubling time of plaque microorganisms as well as the interindivi dual susceptibility to CHX. This study did not allow such assessments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1991a], Delmopinol has also shown promising antiplaque effects in vivo [Collaert et al, 1990], Clinical studies have indicated that the surpragingival plaque formed during rinsing with delmopinol is fluffy and more easily removed than plaque exposed to placebo rinses [Collaert et al, 1992]. The substance has a low antimicrobial profile com pared to chlorhexidine as shown in a clinical cross-over study, where plaque samples collected after 4 days of rins ing twice a day were stained with fluorescent dyes for eval uation of plaque vitality [Rundegren et al, 1992], The plaque-reducing effect achieved with delmopinol thus in dicates other modes of action than pure antimicrobial ef fects of the substance. Delmopinol strongly reduces inter facial tension [Simonsson et al, 1991b] and it may there fore be assumed that delmopinol penetrates the plaque and affects the plaque matrix.…”
mentioning
confidence: 99%